THE EFFECT OF BURNOUT AND SOCIAL SUPPORT ON EMPLOYEE PERFORMANCE AT PT. SULSELBAR BANK - Nureni; Budiyanti, Hety; Haeruddin, M. Ikhwan Maulana (JOURNAL OF HUMANITIES, SOCIAL SCIENCES AND BUSINESS, 2023)
Employee burnout in modern work environments is a growing issue, impacting performance and well-being. Burnout, involving emotional exhaustion and reduced accomplishment, negatively affects employees. Conversely, social support from colleagues and supervisors offers protection against burnout and enhances performance. This study aims to examines the impact of burnout and social support on the performance of employees at PT. Sulselbar Bank. The research follows a quantitative approach and includes a sample of 110 employees. Data collection was done through a questionnaire, and the analysis involved validity and reliability tests, multiple regression analysis, classic assumption tests, T-tests, and F-tests. The findings indicate a negative relationship between burnout (X1) and employee performance (Y), while social support (X2) has a positive influence on employee performance. The multiple linear regression equation is expressed as Y = 31.664 + (-0.394)X1 + 0.358X2. The t-tests show significant results with t- statistic values of -2.584 for X1 and 3.950 for X2, exceeding the t-table value of 1.982. The significance levels are 0.011 for X1 and 0.000 for X2, both below 0.05. Additionally, the F-test demonstrates a significant relationship between the variables, with an F-statistic of 11.102 exceeding the F-table value of 3.08, and a significance level of 0.000 below 0.05. As such, this study highlights that burnout negatively and significantly affects employee performance, while social support has a positive and significant impact. Both burnout and social support jointly and significantly influence employee performance, emphasizing the importance of addressing burnout and fostering a supportive work environment.